2005
DOI: 10.1016/s1525-1578(10)60584-3
|View full text |Cite
|
Sign up to set email alerts
|

Assay Validation for Identification of Hereditary Nonpolyposis Colon Cancer-Causing Mutations in Mismatch Repair Genes MLH1, MSH2, and MSH6

Abstract: Hereditary nonpolyposis colon cancer (HNPCC, Online Mendelian Inheritance in Man (OMIM) 114500) is an autosomal dominant disorder that is genetically heterogeneous because of underlying mutations in mismatch repair genes, primarily MLH1, MSH2, and MSH6. One challenge to correctly diagnosing HNPCC is that the large size of the causative genes makes identification of mutations both labor intensive and expensive. We evaluated the usefulness of denaturing high performance liquid chromatography (DHPLC) for scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Indeed, Tanyi et al reported an HNPCC family with a truncating mutation in MSH2, which when in combination with MSH2 N127S leads to HNPCC phenotype in very early age. 17 Although the majority of the published data discusses MSH2 G322D as a neutral polymorphism, 3,5,[7][8][9][10][11][12] it has also been hypothesized to be a low penetrance allele. 24 This interpretation was supported by the functional analyses conducted with yeast assays, where the putative homologous mutation Msh2 D317D in yeast was reported to cause a moderate, as yet not complete inactivation of MMR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Tanyi et al reported an HNPCC family with a truncating mutation in MSH2, which when in combination with MSH2 N127S leads to HNPCC phenotype in very early age. 17 Although the majority of the published data discusses MSH2 G322D as a neutral polymorphism, 3,5,[7][8][9][10][11][12] it has also been hypothesized to be a low penetrance allele. 24 This interpretation was supported by the functional analyses conducted with yeast assays, where the putative homologous mutation Msh2 D317D in yeast was reported to cause a moderate, as yet not complete inactivation of MMR.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested to be polymorphic when it was not segregating with the cancer phenotype in a family or it was found in healthy control individuals. 3,5,[7][8][9][10][11][12] Contrary to these, it was interpreted as a low penetrance allele based on moderate inactivation of yeast MMR caused by a homologous yeast variant. 13,14 It was also interpreted as pathogenic when it was segregating with the cancer phenotype, and showed loss of MSH2 protein and high microsatellite instability (MSI) in the tumor, 15 or when it was not found in healthy control chromosomes.…”
mentioning
confidence: 99%
“…As previously reviewed, SSCP has no theoretical foundation to predict the separation condition, thus relying entirely upon empirical data for each fragment [26]. On the other hand, dHPLC is based upon similar statistical mechanical calculations of the transition temperature of DNA but has to accurately control the mobile phase and column temperatures [27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the polymer cost would become negligible in a large-scale approach to scan genes or populations. In comparison the running cost for dHPLC is 1$ per injection [27] while our running cost per capillary is calculated to be 0.07$. Table 2, and with a running voltage of 9 kV.…”
Section: Resultsmentioning
confidence: 99%
“…2,6 For this reason, several kinds of different methodologies to analyze the amplicons are now being developed, such as microarray-based methods, 7,8 the capillary electrophoresis method, the DHPLC system, 9,10 and the MCA-based method. 14,17,18 Of these new technologies, promising methods based on the MCA platform are now being developed and some successful results have been reported as clinical use for genotyping single nucleotide polymorphism (SNP) and mutations 8,9,17 and for the identification of infected bacterial and viral pathogens. 18,19 We also tried to establish a rapid, simple, sensitive, and precise method that uses real-time PCR with an MCA platform for scanning K-ras alterations from body fluids with little tumor DNA.…”
Section: Discussionmentioning
confidence: 99%